The Influence Public Interest in BTN Home Ownership Credit (KPR) Financing - Seniorita Seniorita; Ridwan Ridwan; Ratna Ratna; Ilyas Ilyas (Citakonsultindo, 2023)
For credit housing area Banks act as institutions that have an intermediary function to manage the finances of various parties who have excess funds and those who have limited funds which also function as institutions to facilitate payment traffic. This study aims to see the effect of income level, number of dependents, education level, age, and location of the house on people's interest in financing BTN housing loans (KPR) in Minasatene , Pangkep Regency . The data used in this research is primary data. The data collection technique used a questionnaire which was distributed to the community in Minasatene , Pangkep Regency . This research uses normality test , validity and reliability test, and hypothesis test. The results of the study show that there is a significant influence between the variables of income level, number of family dependents, education level, age, and housing location on people's interest in financing BTN Housing Loans (KPR).